2008
DOI: 10.1007/s00420-008-0387-0
|View full text |Cite
|
Sign up to set email alerts
|

Is exposure to silica associated with lung cancer in the absence of silicosis? A meta-analytical approach to an important public health question

Abstract: Necessary further research should concentrate on silica exposures both above and below those that induce silicosis, so that the shape of the exposure-response relationship may be identified, with adjustments for likely confounding factors including silicosis. Time-dependent information on silicosis and on silica dust is required as well as the application of methods like G-estimation to answer the important public health question: Is silicosis a necessary condition for the elevation of silica-associated lung c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 64 publications
0
33
0
1
Order By: Relevance
“…However, Lacasse et al (21) suggested in their meta-analysis that such a threshold might indeed exist between silica-related toxicity and lung cancer, and that it is independent of the pathology from silicosis. Unlike other meta-analyses, (22)(23)(24)(25) Lacasse et al specifically examined lung cancer risk related to cumulative RCS exposures. Lacasse et al reported that statistically significant risks for lung cancer occurred only above a cumulative RCS exposure of 1.84 mg/m 3 -years.…”
Section: Discussionmentioning
confidence: 97%
“…However, Lacasse et al (21) suggested in their meta-analysis that such a threshold might indeed exist between silica-related toxicity and lung cancer, and that it is independent of the pathology from silicosis. Unlike other meta-analyses, (22)(23)(24)(25) Lacasse et al specifically examined lung cancer risk related to cumulative RCS exposures. Lacasse et al reported that statistically significant risks for lung cancer occurred only above a cumulative RCS exposure of 1.84 mg/m 3 -years.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, there is ample evidence that exposure to crystalline silica is associated with an increase in incidence of lung cancers among workers in several occupations (see International Agency for Research on Cancer IARC 1977;Brown, 2009;Erren et al, 2009;Lacasse et al, 2009). There is also a pool of literature that indicates that exposure to silica [by inhalation/other routes (injections)] can affect host resistance to injected/ implanted syngeneic and non-syngeneic tumors (Keller, 1976;Fuji and Murakami, 1983;Sandstrom and Chow, 1987;Gresser et al, 1990); unfortunately, changes in resistance against de novo in situ neoplasias have not been evaluated/ reported in the literature to the same degree.…”
Section: R E V I E W a R T I C L Ementioning
confidence: 99%
“…Nevertheless, this meta-analysis identified three studies that controlled for smoking, estimating a meta-relative risk of 1.0 (95% CI, 0.8 to 1.3); however, for eight remaining studies, the meta-relative risk was slighted but statistically significantly elevated (RR = 1.2; 95% CI, 1.1 to 1.4) with significant heterogeneity noted. 19 In contrast with the lack of support for an association between respirable crystalline silica exposure and lung cancer risk, our study demonstrated clearly and statistically significantly increased risk of radiographic evidence of silicosis (ILO 1/1 or higher) in the highest categories of both average (generally above 0.15 mg/m 3 ) and cumulative (generally >4.0 mg/m 3 -years) exposure, controlling for age, sex, smoking, and duration of employment. Although no formal threshold analyses were performed, this study generated considerable support for a threshold.…”
Section: Discussionmentioning
confidence: 97%
“…The scientific debate continues [8][9][10] and newer research reports and reviews have generated mixed conclusions. [11][12][13][14][15][16][17][18][19] Consequently, a key regulatory question remains as to whether silicosis and lung cancer are prevented at current occupational exposure limits (OELs), which vary by country. In Germany, the OEL had been 0.15 mg/m 3 until a change in regulations suspended this OEL in favor of a health-based OEL (to be determined).…”
mentioning
confidence: 99%